2021
DOI: 10.1007/s11748-021-01630-4
|View full text |Cite
|
Sign up to set email alerts
|

Elective lung resection after treatment for COVID-19 pneumonia

Abstract: A 65-year-old man with coronavirus disease 2019 (COVID-19) was admitted to our hospital. Computed tomography detected bilateral pneumonia with a lung nodule suspicious for lung cancer. Lobectomy was performed 3 months after the treatment for COVID-19 without any complications. The surgical specimen revealed fibrosis below the pleura with a small collection of lymphocytes and intravascular hemorrhagic thrombosis, and no residual RNA was detected. This is the first report describing a surgical specimen after rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Therefore, we decided to perform pulmonary resection, and we expected a long survival time when the patient did well postoperatively without acute exacerbation. Sakai et al reported that organized fibrosis and inflammation might remain for a prolonged period after recovery from COVID-19, even with improved radiological findings (1). The present case had fibrotic change after COVID-19, pathologically.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…Therefore, we decided to perform pulmonary resection, and we expected a long survival time when the patient did well postoperatively without acute exacerbation. Sakai et al reported that organized fibrosis and inflammation might remain for a prolonged period after recovery from COVID-19, even with improved radiological findings (1). The present case had fibrotic change after COVID-19, pathologically.…”
Section: Discussionsupporting
confidence: 42%
“…The spread of COVID-19 infection increased the number of patients treated for lung cancer after COVID-19 infection. There are reports of patients who underwent pulmonary resection for lung cancer after COVID-19 infection ( 1 4 ). The mortality risk with surgery after COVID-19 infection is increased for up to 5–6 weeks after COVID-19 infection ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suspect that, as in the case of other serious respiratory diseases, COVID-19 and the lung damage caused by the disease may affect the early outcomes of lung cancer surgery, including postoperative complications. To our knowledge, only case reports and short case-series were published on the subject up to date [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%